2020
DOI: 10.21203/rs.3.rs-38340/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic factors in patients admitted to an urban teaching hospital with COVID-19 infection

Abstract: BackgroundSevere COVID-19 infection results in a systemic inflammatory response (SIRS). This SIRS response shares similarities to the changes observed during the peri-operative period that are recognised to be associated with the development of multiple organ failure. MethodsElectronic patient records for patients who were admitted to an urban teaching hospital during the initial 7-week period of the COVID-19 pandemic in Glasgow, U.K. (17th March 2020 - 1st May 2020) were examined for routine clinical, laborat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Eighty-seven full-text articles were assessed for eligibility. Twenty-five studies 7,[9][10][11]13,[17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] across 19 countries (Belgium, Brazil, Cyprus, Egypt, France, Greece, Iraq, Italy, Libya, The Netherlands, Poland, Saudi Arabia, Spain, Sudan, Sweden, Switzerland, Turkey, UK and the USA) reporting on 34 628 patients with COVID-19 with frailty assessments, from the early phase of the pandemic, were included in the qualitative and quantitative analysis. Study population sizes were variable, ranging between 23 and 18 234 patients (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eighty-seven full-text articles were assessed for eligibility. Twenty-five studies 7,[9][10][11]13,[17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] across 19 countries (Belgium, Brazil, Cyprus, Egypt, France, Greece, Iraq, Italy, Libya, The Netherlands, Poland, Saudi Arabia, Spain, Sudan, Sweden, Switzerland, Turkey, UK and the USA) reporting on 34 628 patients with COVID-19 with frailty assessments, from the early phase of the pandemic, were included in the qualitative and quantitative analysis. Study population sizes were variable, ranging between 23 and 18 234 patients (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were from the UK (n = 14). 7,[9][10][11]13,18,19,23,24,26,30,33,35,36 All studies reported findings from acute care hospitals, one study specifically on transplant patients 22 and another study from a COVID-19-specific hospital. 27 Five studies 20,24,27,30,31 provided additional data to enable further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations